A benchmark approach to hemorrhage risk management of cavernous malformations. (6th March 2018) - Kashefiolasl, Sepide; Bruder, Markus; Brawanski, Nina; Herrmann, Eva; Seifert, Volker; Tritt, Stephanie; Konczalla, Juergen
Abstract : Objective: Despite the low annual risk of hemorrhage associated with a cavernous malformation (CM) (0.6%–1.1% per year), the risk of rehemorrhage rate and severity of neurologic deficits is significantly higher; therefore, we aimed to evaluate the rupture risk of CMs depending on various factors. Methods: We retrospectively analyzed medical records of all patients with CM admitted to our institution between 1999 and April 2016. Cavernoma volume, location of the lesion, existence of a developmental venous anomaly (DVA), number of cavernomas, and patient characteristics (sex, age, hypertension, and antithrombotic therapy) were assessed. Results: One hundred fifty-four patients with CM were included; 89 (58%) ruptured CMs were identified. In statistical univariable analysis, the existence of a DVA was significantly higher in the ruptured cavernoma group ( p < 0.001; odds ratio [OR] 4.6). A multivariable analysis of all included independent risk factors designated young age (<45 years) ( p < 0.05; OR 2.2), infratentorial location ( p < 0.01; OR 2.9), and existence of a DVA ( p < 0.0001; OR 4.7) with significantly higher risk of rupture in our patient cohort. A separate analysis of these anatomical locations, supratentorial vs infratentorial, indicated that the existence of a DVA ( p < 0.01; OR 4.16) in ruptured supratentorial cases and CM volume (≥1 cm 3 ) ( p < 0.0001; OR 3.5) in ruptured infratentorial cases were significant independent predictors for hemorrhage. Conclusions: Young age (<45 years), infratentorial location, and the presence of a DVA are associated with a higher hemorrhage risk. CM volume (≥1 cm 3 ) and the existence of a DVA were independently in accordance with the anatomical location high risk factors for CM rupture.